Africa: a study in tropical development - Stamp, L. Dudley; Morgan, W. T. W. (New York, Wiley, 1972)
This book exemplifies that man is a part of this world, not apart from it. man must understand his environmental setting and his relationship to it. The aim of this book is a comprehension of Africa, rather than the provision of the latest information.
Bibliography: p. 416-435.
occ 17/01/2019
Loans
Keywords: Africa